Salty Land of India: Genesis, Current Status and Promising Management Interventions for Halting Salinisation and Restoring Productivity - Anil R. Chinchmalatpure (Journal of the Indian Society of Soil Science, 2026)
I feel greatly honoured for the opportunity given by Navsari Chapter of Indian Society of Soil Science, Navsari Agricultural University, Navsari, Gujarat to deliver the 14th Dr. G.S. Sekhon Memorial Lecture during 2024 at Navsari Agricultural University, Navsari. As a tribute to the great soul and eminent soil scientist of the country who has immensely contributed in the area of soil science, I have chosen to speak on the topic “Salty land of India: Genesis, current status and promising management interventions for halting salinisation and restoring productivity”.